Characterization of a basic phospholipase A2-homologeu myotoxin isolated from the venom of the snake Bothrops neuwiedii (yarará chica) from Argentina - Geoghegan, Patricia A. (1999)
Fil: Geoghegan, Patricia A. ANLIS Dr.C.G.Malbrán. Centro Nacional de Control de Calidad de Biológicos. Servicio de Inmunoterapéuticos; Argentina.